2003
DOI: 10.1023/a:1025039809300
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Cognitive distortions are commonly viewed as an important factor in the assessment and treatment of sexual offenders. However, consensus about the operational definition of cognitive distortions and the best instrument to measure such distortions is lacking. This paper evaluates the Bumby MOLEST and RAPE scales as measures of cognitive distortions with patients civilly committed under California's Sexually Violent Predator law. Rapists and child molesters in the current sample endorsed markedly fewer cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…This sample was not appreciably different overall from published findings in other sex offender samples in their profiles on measures of social desirability (Mathie & Wakeling, 2011), cognitive distortions (Arkowitz & Vess, 2003), loneliness (Marshall et al, 1997), and social intimacy (Nunes et al, 2011); on the latter two measures of loneliness and intimacy, the sample's scores were not particularly pathological and were close to the normative means of the nonoffender development samples. The sample scored, on average, below the nonoffender normative mean on This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…This sample was not appreciably different overall from published findings in other sex offender samples in their profiles on measures of social desirability (Mathie & Wakeling, 2011), cognitive distortions (Arkowitz & Vess, 2003), loneliness (Marshall et al, 1997), and social intimacy (Nunes et al, 2011); on the latter two measures of loneliness and intimacy, the sample's scores were not particularly pathological and were close to the normative means of the nonoffender development samples. The sample scored, on average, below the nonoffender normative mean on This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussioncontrasting
confidence: 56%
“…Subsequent research has found other sex offender samples to score lower to varying degrees on both scales. Rape scale means of 50.0 ( SD = 17.8) and 65.7 ( SD = 19.7) were reported in two rapist samples, Molest scale means from 66.0 ( SD = 24.03) to 80.1 ( SD = 21.2) in three child molester samples, and inmate and community controls have been found to score in the 50’s on both measures (Arkowitz & Vess, 2003; Blumenthal, Gudjonsson, & Burns, 1999; Marshall, Marshall, Sachdev, & Kruger, 2003). Bumby (1996) found the Rape and Molest scales to have high internal consistency (α = .97 for both), test–retest reliability ( r = .86 and .84, respectively), and convergent validity with established measures of sex offender cognitions.…”
Section: Methodsmentioning
confidence: 88%
See 2 more Smart Citations
“…Participants indicate their response on a 4-point Likert-type scale ranging from strongly agree to strongly disagree . When compared with similar scales, such as the Abel-Becker Cognition Scale (Abel, Becker, & Cunningham-Rathner, 1984) or the Burt Rape-Myth Acceptance Scale (Burt, 1980), Bumby’s (1996) Rape Questionnaire holds superior psychometric properties (α = .97; see Arkowitz & Vess, 2003; Bumby, 1996; Grady, Brodersen, & Abramson, 2011).…”
Section: Methodsmentioning
confidence: 99%